GOLDFISH AQUARIUM WATER QUALITY CONTROL AND MONITORING SYSTEM USING FLC - Santoso, Budi; Panuntun, Wisnuning Diah (Universitas Muhammadiyah Ponorogo, 2024)
Goldfish is a unique type of carp. Its interesting shape makes it popularly kept by people as a hobby or business. In goldfish farming, it is necessary to manage water quality properly to meet the required water quality criteria to support their life. In this study, a water quality monitoring and control system was developed so that breeders can observe water quality conditions online, and the water quality control process can be carried out automatically. The system utilizes two sensors, namely turbidity sensor and pH sensor, to detect turbidity and pH levels in the aquarium water. The method employed in this study utilizes fuzzy logic to control the filter and pump in the aquarium. The results of the trial showed that turbidity decreased by 21.84%, from an initial value of 16.66 NTU to 13.02 NTU, and pH decreased by 15.26%, from an initial value of 7.86 to 6.66.